Animal-based evidence supports protective activity of bioengineered silver and gold nanomaterials on hepatic and renal function profile parameters - Barabadi, Hamed; Noqani, Hesam; Soltani, Maha; Sabbagh Kashani, Ayeh (Frontiers in Nanotechnology, 2025)
The liver and kidneys are vital organs responsible for essential metabolic and excretory functions, and their protection is a cornerstone of therapeutic innovation. This review highlights the emerging role of eco-friendly, bioengineered silver (AgNPs) and gold nanoparticles (AuNPs) as protective agents for liver and kidney health, based on evidence from animal studies. The discussion emphasizes green synthesis approaches, which offer sustainable and biocompatible routes for nanoparticle production. Key findings reveal the effects of these nanoparticles (NPs) on hepatic enzymes—Aspartate aminotransferase (AST), Alanine transaminase (ALT), and Alkaline phosphatase (ALP)—and renal function markers, including urea and creatinine levels, under both healthy and pathological conditions. In diseased animal models, biosynthesized NPs significantly reduced ALT, AST, ALP, urea, and creatinine levels, demonstrating their protective effects. Conversely, in healthy animals, lower nanoparticle concentrations exhibited no statistically significant impact on these parameters, suggesting their safety at therapeutic doses. This review presents the novelty of bioengineered NPs as potential therapeutic agents for hepatic and renal protection while highlighting the need for further research into their pharmacokinetics and pharmacodynamics to advance clinical translation.